90S pre-ribosome transformation into the primordial 40S subunit - Cheng, Jingdong; Lau, Benjamin; La Venuta, Giuseppe; Hurt, Ed (Science, 2020)
How ribosomes are made - The formation of eukaryotic ribosomes is a complex process that starts with transcription of a large precursor RNA that assembles into a large 90S preribosome, which matures to finally give the 40S small subunit of the ribosome. Cheng et al. and Du et al. give insight into this process, using cryo-electron microscopy to look at intermediates along the pathway. Together, these studies reveal how a cast of molecular players act to coordinate the compositional and structural changes that transform the 90S preribosome into a pre-40S subunit. - Science, this issue p. 1470, p. 1477 - Production of small ribosomal subunits initially requires the formation of a 90S precursor followed by an enigmatic process of restructuring into the primordial pre-40S subunit. We elucidate this process by biochemical and cryo-electron microscopy analysis of intermediates along this pathway in yeast. First, the remodeling RNA helicase Dhr1 engages the 90S pre-ribosome, followed by Utp24 endonuclease-driven RNA cleavage at site A1, thereby separating the 5′-external transcribed spacer (ETS) from 18S ribosomal RNA. Next, the 5′-ETS and 90S assembly factors become dislodged, but this occurs sequentially, not en bloc. Eventually, the primordial pre-40S emerges, still retaining some 90S factors including Dhr1, now ready to unwind the final small nucleolar U3-18S RNA hybrid. Our data shed light on the elusive 90S to pre-40S transition and clarify the principles of assembly and remodeling of large ribonucleoproteins. - The steps that drive the stepwise dissociation of factors in the transition from the 90S to the 40S ribosome subunit are observed. - The steps that drive the stepwise dissociation of factors in the transition from the 90S to the 40S ribosome subunit are observed.
Gesehen am 27.10.2020